Sociolinguistics and language education - Koul Omkar N; Umarani P (Ne Delhi Creative Books, 2001)
This book is a collection of 18 invited papers on applied linguistics with special reference to different aspects of sociolinguistics and language education. The papers are cover wide range of topics like language empowerment, linguistic diversity, langu
Keywords: Sociolinguistics